Membrane Tension Acts Through PLD2 and mTORC2 to Limit Actin Network Assembly During Neutrophil Migration - Diz-Muñoz, Alba; Thurley, Kevin; Chintamen, Sana; Altschuler, Steven J.; Wu, Lani F.; Fletcher, Daniel A.; Weiner, Orion D. (PLOS Biology, 2016)
A mechanosensory biochemical cascade involving phospholipase D2 and mTORC2 coordinates physical forces and cytoskeletal rearrangements to allow efficient polarization and migration of neutrophils.